دورالتمثيل الدبلوماسي في تطوير العلاقات الدبلوماسية في القانون الدولي - Muneer Ali Abdul Rab; Norfadhilah Mohamad Ali; Misbah 'Iyad Misbah 'Abu Khasyim (Islamic Info, 2024)
This paper contributes to shedding light on one of the topics of international relations relating to the role of diplomatic representation in building and developing diplomatic relations in the law of States as affecting one of the most important problems of international relations and diplomacy, as the failure of diplomatic representation to contribute to the building and development of diplomatic relations as a guarantor of peace in the world should not avoid and remove the spectre of wars leading to terrible consequences among the nations of the world, The study established that the exchange of diplomatic representation between States in international law a positive effect that has been credited with averting and defusing many wars. One of the most important findings of this study is the achievement of its objective, through which it sought to demonstrate the great importance of diplomatic representation through its contribution to the development of diplomatic relations between nations and peoples. The study adopted the inductive and historical approach. One of the most notable findings of this study is the " Sources and systems of diplomacy in positive laws are not established because they are subject to events and variables in that their sources are subject to change depending on the circumstances and causes, making diplomatic relations and representation between States unstable and constantly changing according to partial and not substantial variables of disorder and uncertainty. sources ", unlike the sources and systems of diplomacy in the Islamic sharia, their sources are fixed and are not subject to events and variables.